2005
DOI: 10.3852/mycologia.97.1.121
|View full text |Cite
|
Sign up to set email alerts
|

Fomitiporia tenuis and Fomitiporia aethiopica (Basidiomycetes, Hymenochaetales), two undescribed species from the Ethiopian highlands: taxonomy and phylogeny

Abstract: Fomitiporia tenuis sp. nov. and Fomitiporia aethiopica sp. nov. from the Ethiopian highlands are described. Both are characterized by a resupinate habit, globose, dextrinoid basidiospores, cystidioles, and respectively scarcity or absence of hymenial setae. Fomitiporia pseudopunctata and F. robusta are reported also in the same area. The preliminary phylogenetic relationships of F. tenuis, F. aethiopica and F. pseudopunctata are inferred from parsimony analysis based on partial nuclear ribosomal large subunit … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 14 publications
(20 reference statements)
2
17
0
Order By: Relevance
“…The topologies of the trees regarding the recovery and the relative position of the different major generic entities within the poroid Hymenochaetales were identical in both the parsimony and the Bayesian analysis, and in accordance with previous research (Decock et al 2005;Fischer 2001, 2002). In particular, the Phellinus s.s. (BSV/ BPP 90/100%), the Fomitiporia (BSV/BPP 82/100%), the Inocutis (BSV/BPP 100/100%), or the Inonotus sensu Wagner and Fischer clades (BSV/BPP 83/100%) were all recovered and strongly supported.…”
Section: Phylogenetic Analysissupporting
confidence: 84%
See 2 more Smart Citations
“…The topologies of the trees regarding the recovery and the relative position of the different major generic entities within the poroid Hymenochaetales were identical in both the parsimony and the Bayesian analysis, and in accordance with previous research (Decock et al 2005;Fischer 2001, 2002). In particular, the Phellinus s.s. (BSV/ BPP 90/100%), the Fomitiporia (BSV/BPP 82/100%), the Inocutis (BSV/BPP 100/100%), or the Inonotus sensu Wagner and Fischer clades (BSV/BPP 83/100%) were all recovered and strongly supported.…”
Section: Phylogenetic Analysissupporting
confidence: 84%
“…Fomes fomentarius DAOM129034 was used as outgroup in Wagner and Fischer (2001) 93-929 AF311011 ND ND T Type, PT paratype, ND no GenBank accession the nuc-LSU inference (Decock et al 2005). Phellinus sp.…”
Section: Phylogenetic Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Decock et al (2005) also reported a total of four taxa from the highland forests region, and of which Fomitiporia tenuis and F. aethiopica were newly reported to the world. Some other taxa have also been reported by Tuno (2001), Abate (2008), Alemu (2013), Muleta et al (2013), Abate (2014) and Sitotaw et al (2015a) from indigenous forests in different parts of the country.…”
Section: Mushrooms In Indigenous Forestsmentioning
confidence: 99%
“…This genus was split from Phellinus s.l. with Fomitiporia langloisii Murrill as the generic type and was determined to be monophyletic based on molecular data [65,80,81]. [82].…”
Section: Fomitiporiamentioning
confidence: 99%